RouteFinder: real-time optimum vehicle routing using mobile phone network - Ahmadullah, Najiba; Islam, Shahpar; Ahmed, Tarem (© 2015 Institute of Electrical and Electronics Engineers Inc., 2016)
This conference paper was presented in the 35th IEEE Region 10 Conference, TENCON 2015; Holiday Inn, Sands Cotai CentralMacau; Macau; 1 November 2015 through 4 November 2015 [© 2015 Institute of Electrical and Electronics Engineers Inc.] The conference paper's definite version is available at: http://10.1109/TENCON.2015.7372741